Conservative management of Boerhaave’s syndrome: a case report - P., Silambarasan; Prasad, Gaurav; Ram, Vishnu; Kumar, Nirmal (International Surgery Journal, 2022)
The management of esophageal perforation has evolved. The underlying principles of drainage of sepsis, adequate nutrition and repair, or defunctioning of the esophagus remain. We are presenting a case of Boerhaave syndrome, where we have successfully managed conservatively with endoscopic stenting. Endoscopic therapy and VATS are used with increasing frequency and in appropriately selected patients with good results. Careful selection of patients for such procedures are important. Implantation of self-expanding metallic stent in patients with esophageal leak or perforation is a safe and feasible alternative to operative treatment and can lower the interventional morbidity rate.